Process intensification for generating and decomposing formic acid, a liquid hydrogen carrier. Issue 14 (22nd January 2022) - Egbert, Jonathan D.; Grubel, Katarzyna; Howe, Daniel T.; Weber, Robert S.; Agarwal, Arun S.; Brix, Todd
Abstract: We preview two processes that facilitate using formic acid (HCOOH) as a liquid hydrogen carrier to store renewably‐generated electrical energy and then release it to generate electrical power cleanly for backup or emergency applications. First, we show that simultaneously oxidizing an organic solute (typically a waste stream) can assist the electrochemical synthesis of formic acid by lowering the cell potential. The electrolyser comprises a hybrid 3‐chamber PEM stack that reduces CO₂ via a gas‐diffusion cathode boosted by the oxidation of aqueous methanol. However, the extent of the boosting needs to be optimized across the whole operation of the cell. Next, we present results from an intensified reactor for decomposing formic acid back into H₂ and CO₂ at elevated pressure so that the H₂ can be used in a fuel cell. The reactor combines three operations: Vaporization of the formic acid, its decomposition, and separation of the product stream. Their close coupling affords energy savings and a compact design that could be mounted on a mobile skid. We briefly discuss the electrode catalyst that facilitates the first process and two thermally activated catalysts (Ir supported on covalent triazine framework and Pd supported on carbon) that enable the second process.